PENGELOLAAN PEMBIMBINGAN SISWA DI SMA NEGERI 1 MAMUJU KABUPATEN MAMUJU - Yunus, Muhammad (Pascasarjana Universitas Negeri Makassar, 2014)
The study aimed at examining the planning, the implementation, and the evaluation of guiding and counseling services. This study was a qualitative research which conducted at SMAN 1 Mamuju in Mamuju district. The data sources of the study were determined with the consideration that the chosen informants had sufficient knowledge and able to explain the real condition which related to the study as well as they available time to be interviewed in the process of collecting the data. The informants were the coordinator of guiding and counseling, teachers of guiding and counseling, the principal, teachers of subject matter, and students. Data were collected through interview, documentation, and observation. Data were analyzed qualitatively and the data were verified using triangulation and member check.The results of the study were (1) the planning of guiding and counseling services at SMAN 1 Mamuju in Mamuju district showed that series of activities had been conduted, proved by the implementation of feasibility study/analysis of environment, the arrangement of guiding and counseling program, the implementation of consultation program among teachers of guiding and counseling, and partnership with subject matter teachers as wellas the implementation of task organization and the responsibility of guiding and counseling teachers; (2) the implementation of guiding and counseling at SMAN 1 Mamuju in Mamuju district showed that teachers of guiding and counseling had been conducted, proved by the implementation of basic services activities, responsive services activities, and individual plan activities; and (3) the evaliation of guiding and counseling services at SMAN 1 Mamuju in Mamuju district showed that the implementation of evaluation of guiding and counseling activities had not been conducted well and not systematic yet, proved by the implementation of evaluation activities which was conducted in a form of a report was not yet described the result aspect